Diagnostic Value of Transthoracic Echocardiography in Patients with Anomalous Origin of the Left Coronary Artery from the Pulmonary Artery - Li, R.; Sun, Zhonghua; Yang, J.; Yang, Y.; Li, Y.; Leng, Z.; Liu, G.; Pu, L. (Lippincott Williams & Wilkins, 2016)
Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary abnormality associated with early infant mortality and sudden death in adults. Transthoracic echocardiography (TTE) plays an important role in early detection and diagnosis of ALCAPA as a noninvasive modality. However, its diagnostic value is not well studied. The purpose of this study is to determine the performance of TTE in the diagnostic assessment of ALCAPA as compared with coronary CT and invasive coronary angiography. A total of 22 patients (13 women and 9 men, mean age, 12.9±19.5 years) with ALCAPA who underwent echocardiographic examination for clinical diagnosis were retrospectively reviewed and analyzed. Transthoracic echocardiographic features of ALCAPA were analyzed and its diagnostic value was compared with invasive coronary angiography and coronary CT angiography (CTA) with surgical findings serving as the gold standard. Surgery was performed in all of the patients to establish the dual coronary artery system. Five underwent the Takeuchi procedure and 17 had re-implantation of the anomalous left coronary artery. Of 20 patients, echocardiographic diagnoses were in good agreement with findings at surgery, resulting in the diagnostic accuracy of 90.9%. Two cases were misdiagnosed-one as the right coronary artery to pulmonary artery fistula and the other as rheumatic heart disease. The echocardiographic features of these patients with ALCAPA included: abnormal left coronary ostium arising from the pulmonary trunk with retrograde coronary artery flow in 20 patients; enlargement of the right coronary artery in 17 patients; abundant intercoronary septal collaterals in 17 patients; and moderate and significant mitral regurgitation in 14 patients. The diagnostic accuracy of invasive coronary angiography (in 17 patients) and coronary CTA (in 9 patients) was 100%. This study shows that TTE is an accurate, noninvasive imaging modality for displaying the origin of coronary arteries and demonstrating the coronary courses as well as other associated abnormalities in patients with ALCAPA.